Incidences and reporting rates of incidental findings on lumbar, thoracic, and cervical spinal magnetic resonance images and extra-neuronal findings on brain magnetic resonance imagesö - Kızılgöz, Volkan; Aydın, Hasan; Sivrioğlu, Ali Kemal; Özcan, Ümit Can; Menderes, Utku; Karayol, Sunay Sibel; Erdem, Ahmet (The European Research Journal, 2019)
Objective: This study aimed to evaluate the incidence rates, reporting rates, and the best imaging plane and sequence for incidental findings in patients undergoing spinal and brain magnetic resonance (MR) imaging. Methods: Three experienced radiologists retrospectively re-evaluated the MR images of 1056 consecutive patients. Results: The incidence rates for extraspinal incidental findings for the images of the lumbar, thoracic, and cervical spine, and extra-neuronal incidental findings on MR images of the brain were 35.47%, 32.25%, 29.16%, and 54.35%; respectively, with reporting rates of incidental findings for these examinations of 31.47%, 8.33%, 29.50%, and 59.62%; respectively. For all examination types, the T2-weighted sequence and the axial plain were the best to reveal the incidental findings of MR examinations, other than that of the cervical spine. Conclusions: Incidental findings, which are commonly detected during routine spinal and brain MR evaluations, are occasionally omitted from formal radiological reports in daily practice. We strongly recommend checking the T2-weighted axial plane for MR imaging of the lumbar, thoracic spine and brain and taking a second look at the T2-weighted sagittal plane MR images of the cervical spine during radiological evaluations.